POSSIBILITIES OF VACUUM-INSTILLATION THERAPY WITH DIMEXIDUM AND BETADINE IN THE TREATMENT OF PURULENT WOUNDS - E. V. Razmakhnin; V. A. Shangin; O. G. Kudryavtseva; D. Y. Okhlopkov (Acta Biomedica Scientifica, 2017)
With the use of vacuum therapy in the treatment of purulent wounds, it is not possible to actively localize the microflora in the wound, since the last is for a long time covered by an insulating sealed bandage. In addition, unlike with traditional methods of treating wounds with daily dressings, there is no effect of "washing away" detritus, necrotic masses, accumulations of leukocytes. The aim of the work was to develop a technique for vacuum-instillation therapy of wounds using dimexidum and betadine and to evaluate its effectiveness in comparison with the isolated application of controlled negative pressure in patients with purulent wounds of various origins. 58 patients with chronic purulent wounds, trophic ulcers with atherosclerotic lesions of the vessels of the extremities and diabetic angiopathy were examined. The first group of patients received isolated vacuum therapy, the second group was managed with vacuum-instillation therapy with dimexidum and betadine, the control group received traditional treatment with water-soluble ointments. Evaluation of the results of treatment was based on growth of granulation tissue, reduction of defect size, and level of cytokines in traumatic discharge. Vacuum therapy significantly improves the course of the wound process, which leads to faster cleaning, granulation of the defect and a decrease in its size. When added to NPWT instillations of antiseptics, anti-inflammatory, antioxidant and anabolic effects are enhanced, which facilitates more pronounced regenerative response and, accordingly, a reduction in the duration of treatment.